School-age children and adolescents suspected of having been to be infected with pertussis in Japan. Issue 20 (11th May 2018) - Yasui, Yosuke; Mitsui, Toshikatsu; Nishimura, Tomoyasu; Uchida, Keiko; Inokuchi, Mikako; Mori, Masaaki; Tokumura, Mitsuaki; Nakayama, Tetsuo
Highlights: Antibodies against pertussis were investigated in school-age children in Japan. Positive rate of PT antibody was <40% at 6–7 years of age and higher by age. Mean titer of anti-PT IgG antibodies was higher among older school-age groups. The data strongly suggests the additional vaccination before 6–7 years of age. Abstract: Many countries including Japan have adapted acellular pertussis vaccines combined with diphtheria and tetanus toxoids (DTaP). DTaP vaccine coverage is approximately >90%, but pertussis re-emergence has been observed since 2000 in Japan. In the present study, anti-pertussis antibodies were investigated among school-age children and adolescents from 2013 to 2015. The positive rate of anti-pertussis toxin (PT) antibodies was higher among children aged 12–13 years (60.0%. 95%CI; 56.0–63.9%) in 2014 and 18–19 years (73.0%. 95%CI; 61.4–82.6%) in 2013, compared with 6–7 years (47.1%. 95%CI; 40.7–53.6%). The mean PT antibody titer was higher among children aged 12–13 years (23.8 EU/ml. 95%CI; 21.9–25.8) in 2014 and 18–19 years (29.3 EU/ml. 95%CI; 23.0–35.6) in 2013, compared with 6–7 years (18.3 EU/ml. 95%CI; 15.5–21.2). Distributions of pertussis antibodies and mean titers at their same grade of school-age were similar from 2013 to 2015. Although school-age children were immunized with 4 doses of DTaP, the data suggested the decay of vaccine-acquired immunity and possibility of asymptomatic infection in school age, indicating the additional DTaP vaccination before the entry of elementary school, preventing household contact.